Current research progress of local drug delivery systems based on biodegradable polymers in treating chronic osteomyelitis - Liu, Yixiu; Li, Xu; Liang, A. (Frontiers in Bioengineering and Biotechnology, 2022)
Chronic osteomyelitis is one of the most challenging diseases in orthopedic treatment. It is usually treated with intravenous antibiotics and debridement in clinical practice, which also brings systemic drug side effects and bone defects. The local drug delivery system of antibiotics has the characteristics of targeted slow release to the lesion site, which can replace systemic antibiotics, reduce the toxic and side effects of drugs, increase the local drug concentration, achieve sound bacteriostatic and bactericidal effects, and promote bone healing and bone formation. Currently, PMMA beads are used in treating chronic osteomyelitis at home and abroad, but the chain beads need to be removed after a second operation, inconveniences patients. Biodegradable materials have been extensively studied as optimal options for antibiotic encapsulation and delivery, bringing new hope for treating chronic osteomyelitis. This article reviews the research progress of local drug delivery systems based on biodegradable polymers, including natural and synthetic ones, in treating chronic osteomyelitis.